3D-Language Acquisition Test (3D-LAT) - Herlekar, Geetha (Journal of All India Institute of Speech and Hearing)
The objective of the present study was (i) to validate the data obtained on 3 children in terms of language acquisition on a larger population and (ii) to obtain normative data for the same population for use in the evaluation of language acquisition in young children.